Antihuman Immunodeficiency Virus Type 1 (HIV-1) Activity of Rare Earth Metal Complexes of 4-Hydroxycoumarins in Cell Culture (Bioinorganic Chemistry and Applications)
The cerium Ce(III), lanthanum La(III), and neodymium Nd(III) complexes with 4-hydroxy-3-(3-oxo-1-phenylbutyl)-2H-1-benzopyran-2-one (warfarin) (W) and 3, 3 ′ -benzylidenebis[4-hydroxycoumarin] (1) were synthesized and studied for the first time for cytotoxicity (on MT-2 cells) and as anti-HIV agents under acute and chronic infection. The complexes were characterized by different physicochemical methods: mass spectrometry, ¹H NMR, ¹³C NMR, and IR spectroscopy. The spectra of the complexes were interpreted on the basis of comparison with the spectrum of the free ligands. Anti-HIV effect of the complexes/ligands was measured in MT-2 cells by microtiter infection assay. Detection of endogenous reverse transcriptase (RT) activity and RT processivity by PCR indicative for proviral DNA synthesis demonstrated that anti-HIV activity has not been linked to early stages of viral replication. No effect on late steps of viral replication has been found using cells chronically producing HIV- 1 LAI virus. La(W) demonstrated anti-HIV activity (IC50=21.4μM) close to maximal nontoxic concentration. Nd(W), Ce(1), and Nd(1) demonstrated limited anti-HIV potency, so none of the complexes seems appropriate to be used in clinic. Further targeting of HIV-1 inhibition by La(W) is under progress.